Molecular cloning and functional analysis of SUT-1, a sulfate transporter from human high endothelial venules - Girard, Jean-Philippe (The National Academy of Sciences, 1999)
High endothelial venules (HEV) are specialized postcapillary venules found in lymphoid organs and chronically inflamed tissues that support high levels of lymphocyte extravasation from the blood. One of the major characteristics of HEV endothelial cells (HEVEC) is their capacity to incorporate large amounts of sulfate into sialomucin-type counter-receptors for the lymphocyte homing receptor L-selectin. Here, we show that HEVEC express two functional classes of sulfate transporters defined by their differential sensitivity to the anion-exchanger inhibitor 4,4′-diisothiocyanostilbene-2,2′-disulfonic acid (DIDS), and we report the molecular characterization of a DIDS-resistant sulfate transporter from human HEVEC, designated SUT-1. SUT-1 belongs to the family of Na(+)-coupled anion transporters and exhibits 40–50% amino acid identity with the rat renal Na(+)/sulfate cotransporter, NaSi-1, as well as with the human and rat Na(+)/dicarboxylate cotransporters, NaDC-1/SDCT1 and NaDC-3/SDCT2. Functional expression studies in cRNA-injected Xenopus laevis oocytes showed that SUT-1 mediates high levels of Na(+)-dependent sulfate transport, which is resistant to DIDS inhibition. The SUT-1 gene mapped to human chromosome 7q33. Northern blotting analysis revealed that SUT-1 exhibits a highly restricted tissue distribution, with abundant expression in placenta. Reverse transcription–PCR analysis indicated that SUT-1 and the diastrophic dysplasia sulfate transporter (DTD), one of the two known human DIDS-sensitive sulfate transporters, are coexpressed in HEVEC. SUT-1 and DTD could correspond, respectively, to the DIDS-resistant and DIDS-sensitive components of sulfate uptake in HEVEC. Together, these results demonstrate that SUT-1 is a distinct human Na(+)-coupled sulfate transporter, likely to play a major role in sulfate incorporation in HEV.